Metody estymacji w ujęciu dekompozycyjnym - Rybicka, Aneta (Estimation methods in decompositional approach, 2005)
One of the most important elements of marketing research become research of attitude and preference of consumers. Knowledge about their attitudes and preferences and adequate adapting products or services to this preferences and attitudes by companies guarantees to achieving of profits. One of the stage of research procedure is choice of estimation method. This choice depend, first of all, on measurement scale. In a paper presented selected estimation methods used in decompositional approach, that is ordinary least squares (that we use in conjoint analysis) and logit models (used in discrete choice method), their characteristic and application in recent years.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Ekonometria (15); 2005; nr 1096, s. 56-68